Die Golem . The Golem - Wegener, Paul
Duration: 01:25:00 A relic certainly, but a fascinating one, "Der Golem" is perhaps the screen's first great monster movie. Though it was actually the third time director-star Paul Wegener had played the eponymous creation, the earlier efforts (sadly lost) were rough drafts for this elaborate dramatization of the Jewish legend. When the Emperor decrees that the Jews of mediaeval Prague should be evicted from the ghetto, a mystical rabbi creates a clay giant and summons the demon Astaroth who breathes out in smoky letters the magic word that will animate the Golem. Intended as a protector and avenger, the Golem is twisted by the machinations of a lovelorn assistant and, like many a monster to come, runs riot, terrorizing guilty and innocent alike until a little girl innocently ends his rampage. Wegener's Golem is an impressively solid figure, the Frankenstein monster with a slightly comical clay wig. The wonderfully grotesque Prague sets and the alchemical atmosphere remain potent.